THE IMPORTANCE OF MATHEMATICAL TASKS IN STEAM EDUCATION A WORLD EXPERIENCE (World Bulletin of Social Sciences, 2023)
This article discussed the importance of math tasks in Steam learning in the context of world experience. Mathematics is the means and basis for the solid development of learning skills, logical thinking and reasoning. Without these strong skills in the XXI century, college programs leading to STEM careers will either be unattractive to high school graduates, or worse, will produce below-average talent. STEAM-based learning provides students with the tools and methods to explore new and creative ways to solve problems, map data, innovate, and connect multiple domains. It teaches them to think outside the box